2012 IEEE Conference on Computational Intelligence for Financial Engineering &Amp; Economics (CIFEr) 2012
DOI: 10.1109/cifer.2012.6327784
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Temporal Memory-based algorithmic trading of financial markets

Abstract: Abstract-This paper explores the possibility of using the Hierarchical Temporal Memory (HTM) machine learning technology to create a profitable software agent for trading financial markets. Technical indicators, derived from intraday tick data for the E-mini S&P 500 futures market (ES), were used as features vectors to the HTM models. All models were configured as binary classifiers, using a simple buy-and-hold trading strategy, and followed a supervised training scheme. The data set was divided into a trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Results showed an increase in accuracy for both datasets (73.5 percent versus 71.2 percent and 86.7 percent versus 84.2, respectively), compared with the original LLC model. Gabrielsson, Konig, and Johansson (2012) aimed at leveraging HTM to create a profitable software agent for trading financial markets. A supervised training scheme was used for HTM, with intraday tick data for the E-mini Standard and Poor's 500 futures markets.…”
Section: Related Workmentioning
confidence: 99%
“…Results showed an increase in accuracy for both datasets (73.5 percent versus 71.2 percent and 86.7 percent versus 84.2, respectively), compared with the original LLC model. Gabrielsson, Konig, and Johansson (2012) aimed at leveraging HTM to create a profitable software agent for trading financial markets. A supervised training scheme was used for HTM, with intraday tick data for the E-mini Standard and Poor's 500 futures markets.…”
Section: Related Workmentioning
confidence: 99%
“…In [3], the predictive performance of the HTM technology was investigated within algorithmic trading of financial markets. The study showed promising results, in which the HTM-based algorithm was profitable across bullish-, bearish and horizontal market trends, yielding comparable results to its neural network benchmark.…”
Section: Related Workmentioning
confidence: 99%
“…It borrows concepts from neural networks, Bayesian networks and makes use of spatiotemporal clustering algorithms to handle noisy inputs and to create invariant representations of patterns discovered in its input stream. In a previous paper [3], an initial study was carried-out where the predictive performance of the HTM technology was investigated within algorithmic trading of financial markets. The study showed promising results, in which the HTMbased algorithm was profitable across bullish-, bearish and horizontal market trends, yielding comparable results to its neural network benchmark.…”
Section: Introductionmentioning
confidence: 99%